Intraocular lenses: Antibacterial Nanopillar Array for an Implantable Intraocular Lens (Adv. Healthcare Mater. 18/2020). Issue 18 (23rd September 2020) - Choi, Goro; Song, Younseong; Lim, Hyungjun; Lee, Song Ha; Lee, Hyung Keun; Lee, Eunjung; Choi, Bong Gill; Lee, Jae Jong; Im, Sung Gap; Lee, Kyoung G.
Abstract : In article 2000447 by Sung Gap Im, Kyoung G. Lee and co‐workers, a novel approach is provided for the monolithic antibacterial functionalization of an intraocular lens (IOL) using an ionic polymer‐coated nanopillar array (NPA). The ionic polymer‐coated NPA exhibits excellent antibacterial performance through rupturing and destabilizing the bacterial membrane. The proposed strategy can prevent potential bacterial infection and IOL replacement after a cataract surgery.